Empowerment of Family Communications in Engagement Effectiveness of Family Members in Pandemic Times - S. Bekti Istiyanto; Ifan Iskandar; Maulina Larasati Putri; Kiki Dwi Arviani; Hana Hanifah (Journal of Digital Marketing and Communication, 2022)
Families are essential to a healthy and prosperous society. During a pandemic, the family's role in the development of family elements is diminished. The research question is whether family communication exists regarding family members' engagement during a pandemic. The study's objective was to ascertain the effect of family communication on family members' involvement during a pandemic. The term "family communication" refers to the exchange of information between family members and the involvement of family members. The researchers distributed validated and reliable questionnaires to respondents. The findings of this study indicate that family communication has a strong correlation with family member involvement. In this study, the null hypothesis was rejected. As a result, the alternative research hypothesis was accepted. All aspects of family communication that have a positive value, such as words, gestures, voice intonation, actions to instill hope, expressions, and mutual understanding, have a strong relationship with the two variables.The research concludes and suggests that all family communication components possess positive descriptive elements and thus exert a strong influence on family members' participation in this study.